Pengaruh Efikasi Diri terhadap Tokoh Desi dan Aini dalam Novel Guru Aini Karya Andrea Hirata - Anak Agung Ayu Ulantari; I Nyoman Weda Kusuma; I Ketut Nama (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2026)
This study aims to analyze the influence of self-efficacy on the motivation of the characters Desi and Aini in Andrea Hirata's novel Guru Aini based on Albert Bandura's Social Cognitive Theory. This research employed a qualitative descriptive method with a literary psychology approach. The research data consisted of textual excerpts illustrating the characters' behaviors, thoughts, and attitudes, which were collected through literature review using reading, observation, and note-taking techniques. Data were analyzed based on the four sources of self-efficacy, namely mastery experiences, vicarious experiences, verbal persuasion, and physiological and emotional states. The findings reveal that the motivation of both Desi and Aini is shaped by the interaction of these four sources of self-efficacy. Desi's self-efficacy is reflected in her perseverance, idealism, self-evaluation, and commitment as an educator despite encountering various teaching challenges. Meanwhile, Aini's self-efficacy develops through her learning experiences, Guru Desi's exemplary role, verbal encouragement from her social environment, and a strong emotional drive to fulfill her aspiration of becoming a doctor in order to treat her father. Overall, this study demonstrates that self-efficacy plays a crucial role in developing and sustaining the motivation of both characters, while also contributing to the advancement of literary psychology studies by providing a deeper understanding of the psychological dynamics of literary characters.